The economic contribution of non-timber forest products to South Korean mountain villager livelihoods - VAN GEVELT, Terry (Institutional Knowledge at Singapore Management University, 2013)
Since 1995, the Korea Forest Service has supported the commercialisation of non-timber forest products (NTFPs) as a means to improve the livelihoods of mountain villagers. There is, however, very little data at the household-level concerning the economic contribution of NTFPs to mountain villager livelihoods. This study uses village-level and household-level data collected from nine mountain villages in Gangwon and North Gyeongsang provinces to (1) reveal the economic contribution of NTFPs to mountain villager livelihoods and (2) analyse the reasons for differing degrees of household reliance on NTFPs. Data show that the mean contribution of NTFPs to households is 4.85% of household revenue. However, clustering households by share of NTFP revenue shows that the mean contribution of NTFPs for the tertile of households with the highest share of NTFP revenue is 21.53% of household revenue. Data suggest a positive correlation between household revenue and NTFP revenue. Poorer households are the most reliant on NTFPs and tend to generate the majority of their NTFP revenue from cultivated NTFPs. A discrete choice model informed by the sustainable livelihoods framework and estimated using a multinomial logit regression suggests that contextual factors and institutions have a stronger effect on a household's degree of reliance on NTFPs than assets. Findings suggest that policies supporting NTFP commercialisation should actively target poorer households and take into account each village's contextual factors and institutions.